Nursing Care for The Risk of Violent Behavior in Schizophrenic Patient - Nadiefa Ashari Harliyanti; Arni Nur Rahmawati; Prasati Adriani (Genius Journal, 2022)
Objective: This study aims to describe the nursing care of the risk of violent behavior in patients with schizophrenia in RSUD Banyumas. Method: In this study, the researchers applied a case study method and the data collection techniques used were interviews, observations, and documentation studies. Result: The results showed that after being given therapeutic communication for three days, the patients were able to control their emotions with assistance from the nurses and the patients seemed to be able to interact well. Conclusion: Based on the results of the study, it can be concluded that nursing actions of deep breathing relaxation, and distraction by hitting the pillow can reduce the emotional problems of people with the risk of violent behavior.